Nutritional value and sensory acceptability of fish burger prepared with flaxseed flour - Duman, Muhsine (Soc Brasileira Ciencia Tecnologia Alimentos, 2022)
Flaxseed flour has gained popularity among consumers worldwide due to the various nutrients and bioactive compounds it contains. The aim of this study was to evaluate the cooking yields, the nutritional value, and the sensory acceptability of fish burgers with an addition of flaxseed flour in different concentrations (5, 10, and 15%). The results showed that the cooking yields (79.2%) of the F0 (control) group was lower (p < 0.05) than the burger to which flaxseed four was added. The flaxseed addition had some effect on the nutritional value of the fish burgers. The flaxseed rates increased the protein, but the fat content did not change significantly. The control group had the highest moisture and the lowest ash. Fish burgers made with the addition of 15% flaxseed flour had the highest energy value and the lowest moisture. There was no statistically significant difference among the fish burger groups with respect to sensory properties. The general acceptability scores showed that the group with the most positive response was the one containing 10% flaxseed flour fish burgers.
Keywords: fish burgers; flaxseed flour; acceptance